Differential GMSK Receivers with Phase Control for Narrowband Radio Communications - N. Riley (Radioengineering, 1998)
An implementation method for differential Gaussian Minimum Shift Keying receivers with Phase Control is presented. It is shown that in such receivers the effect' of InterSymbol Interference (ISI) on the signal, caused by the adjacent bits is reduced by introducing Phase Control in accordance with the data stream. This results in improved system performance, particularly at low values of time-bandwidth product of the premodulation gaussian filter where ISI is high. With the application of this technique the performance of differential receiver is enhanced to a level where it is comparable to that of coherent receiver and yet avoids the problems associated with the complex carrier recovery in the latter case.